Impact of acute consumption of beverages containing plant-based or alternative sweetener blends on postprandial appetite, food intake, metabolism, and gastro-intestinal symptoms: Results of the SWEET beverages trial. (1st May 2023) - Almiron-Roig, Eva; Navas-Carretero, Santiago; Castelnuovo, Gabriele; Kjølbæk, Louise; Romo-Hualde, Ana; Normand, Mie; Maloney, Niamh; Hardman, Charlotte A.; Hodgkins, Charo E.; Moshoyiannis, Hariklia; Finlayson, Graham; Scott, Corey; et al.
Abstract: Project SWEET examined the barriers and facilitators to the use of non-nutritive sweeteners and sweetness enhancers (hereafter "S&SE") alongside potential risks/benefits for health and sustainability. The Beverages trial was a double-blind multi-centre, randomised crossover trial within SWEET evaluating the acute impact of three S&SE blends (plant-based and alternatives) vs. a sucrose control on glycaemic response, food intake, appetite sensations and safety after a carbohydrate-rich breakfast meal. The blends were: mogroside V and stevia RebM; stevia RebA and thaumatin; and sucralose and acesulfame-potassium (ace-K). At each 4 h visit, 60 healthy volunteers (53% male; all with overweight/obesity) consumed a 330 mL beverage with either an S&SE blend (0 kJ) or 8% sucrose (26 g, 442 kJ), shortly followed by a standardised breakfast (∼2600 or 1800 kJ with 77 or 51 g carbohydrates, depending on sex). All blends reduced the 2-h incremental area-under-the-curve (iAUC) for blood insulin (p < 0.001 in mixed-effects models), while the stevia RebA and sucralose blends reduced the glucose iAUC (p < 0.05) compared with sucrose. Post-prandial levels of triglycerides plus hepatic transaminases did not differ across conditions (p > 0.05 for all). Compared with sucrose, there was a 3% increase in LDL-cholesterol after stevia RebA-thaumatin (p < 0.001 in adjusted models); and a 2% decrease in HDL-cholesterol after sucralose-ace-K (p < 0.01). There was an impact of blend on fullness and desire to eat ratings (both p < 0.05) and sucralose-acesulfame K induced higher prospective intake vs sucrose (p < 0.001 in adjusted models), but changes were of a small magnitude and did not translate into energy intake differences over the next 24 h. Gastro-intestinal symptoms for all beverages were mostly mild. In general, responses to a carbohydrate-rich meal following consumption of S&SE blends with stevia or sucralose were similar to sucrose.